Análisis de la explotación del pez espada Xiphias gladius y de la tintorera Prionace glauca por la flota palangrera catalana durante el periodo 2010-2015 en el Mediterráneo occidental - Biton Porsmoguer, Sebastián (Revista de Biología Marina y Oceanografía, 2019)
Swordfish and blue shark are species exploited by the Catalan longline fleet. The number of longliners registered in Catalonia increased between 2010 and 2015. The period when is not allowed to fish swordfish from 2014 would not meet the biological objectives. This species is overexploited in the Mediterranean Sea. Landed quantities of blue shark increased and could illustrate a possible recovery in this marine zone. The authorities must establish measures for sustainable exploitation.